If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -7) = -21 + 12z Combine like terms: 4 + -7 = -3 3(-3) = -21 + 12z Multiply 3 * -3 -9 = -21 + 12z Solving -9 = -21 + 12z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12z' to each side of the equation. -9 + -12z = -21 + 12z + -12z Combine like terms: 12z + -12z = 0 -9 + -12z = -21 + 0 -9 + -12z = -21 Add '9' to each side of the equation. -9 + 9 + -12z = -21 + 9 Combine like terms: -9 + 9 = 0 0 + -12z = -21 + 9 -12z = -21 + 9 Combine like terms: -21 + 9 = -12 -12z = -12 Divide each side by '-12'. z = 1 Simplifying z = 1
| 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 | | 2/3(3x-9)=1/4(4x-12) | | 13r-8-12= | | 10x+5+8=12x-3x+8 | | 9=4x-x | | 6(1-2m)-4(m+1)=50 | | v=x(19-2x)(8.5-2x) | | 600=4x+8x | | 600=4x*8x | | -143=-11*x | | -6(5-7r)+4(-4r-5)=28 | | 15x-3-4x=21x-8-25 | | 4(x)-4(2x)=600 | | 3x+5x-5=2(4x+1) | | -9+4r=4t-3-6 | | 3x^3-4x^2+9x-12=0 | | 1+4x+8x=-11 | | -17*x=-204 | | (x+3)/5=(3x+1)/4 | | 12x+1=12x-6 | | 8(x-2)+4x=9(x+5)-22 | | 3(x-1)=2x-3+x | | 2x-3/2x+x+3/3x | | 2y=60k | | X/2-1/3=8 | | 2v+18=16-4-(v+7) | | 3x+2=18-x | | 5+1.5(2d-5.4)=0.5 |